Analisis Efektivitas Distribusi Zakat pada Baitulmal Bank Syariah Indonesia - Akhmad Arif Rifan; Rofiul Wahyudi; Oril Presti Nurani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The Zakat Management Organization is a non-profit organization that is expected to be managed to provide more comprehensive benefits to the community, one of which is Baitulmaal, which is managed by a sharia bank. This study aims to analyze the effectiveness of the distribution of zakat in baitulmaal Indonesian Islamic banks. The research method uses a quantitative approach with a descriptive design. The population of this research is all Baitulmal Islamic banks in Indonesia. The sample selection in this study used purposive sampling with the following criteria: limited to Baitulmal Islamic banks, including in the category of book banks 3 & 4, have published financial data, do not include other Baitulmal institutions or government national zakat institutions. Based on the criteria, the samples selected according to the requirements are Baitul Maal Muamalat (BMM) Bank Muamalat Indonesia, BSM Umat, BRI Baitul Maal Foundation (YBM), Hasanah Titik Foundation (YHT) BNI Syariah. Measurement of Baitulmal Islamic banks' effectiveness on the dimensions of the intermediation function in the Zakat Core Principle (ZCP) Model. This study's findings indicate that in 2016 the level of effectiveness was in the fairly significant category. Meanwhile, 2017 and 2018 showed an increase in the significant type. The effectiveness of baitulmaal during this research period indicates the importance of management to improve performance so that zakat funds can be more targeted and useful